AMBER ALERT: creation, implementation and perspectives for Brazil - Sotto Mayor, Talita; De Oliveira Dian, Mauricio (Revista Interface Tecnológica, 2025)
Created out of an extreme need related to the increase in child abductions in the United States, the Amber Alert system was initially developed locally in the state of Texas. Due to its success, it was later expanded nationwide. In the beginning, local radio stations and television channels were used to disseminate news about missing children, but in 2002, a national system was developed and implemented. This system proved to be extremely effective over the years, showing progressively higher recovery rates for missing children. With the Amber Alert integrated into instant messaging systems and social media notifications, the statistics in favor of the system and its growing acceptance by the American population, the system gained effectiveness and success. As a result, several other countries in the Americas and Europe became interested in adopting it, each with its own methods and names. Through bibliographic research on the subject, this article aims to provide information on the effectiveness of the Amber Alert in recovering missing children and the importance of its implementation in Brazil. The justification lies in the belief that, with the adoption of this system in Brazil starting in August 2023, the country will be able to achieve the same success in the rapid recovery of missing children that many other countries have already experienced. The outlook is positive, with several Brazilian states expressing interest in implementing Amber Alert, and the trend is for the system to reach a large part of the national territory.
Keywords: amber alert; recovery of missing children; implementation in brazil